Dexamethasone Increases the Anesthetic Success in Patients with Symptomatic Irreversible Pulpitis: A Meta-Analysis - Lorenzo Franco-de la Torre; Eduardo Gómez-Sánchez; Nicolás Addiel Serafín-Higuera; Ángel Josabad Alonso-Castro; Sandra López-Verdín; Nelly Molina-Frechero; Vinicio Granados-Soto; Mario Alberto Isiordia-Espinoza (MDPI AG, 2022)
Inferior alveolar nerve block (IANB) has a high failure rate in subjects with symptomatic irreversible pulpitis (SIP). It has been suggested that drugs with anti-inflammatory activity could improve the efficacy of the anesthetic used for IANB. The aim of this study was to assess the effect of dexamethasone on the success of dental anesthesia in patients with SIP. An information search was performed using PubMed and Google Scholar. The risk of bias of the included studies was evaluated with the Cochrane Collaboration's risk-of-bias tool. The anesthetic success rate, pain intensity (VAS), and adverse effects were extracted. Data were analyzed using the Mantel-Haenszel test and odds ratio or the inverse variance and standardized mean difference. Dexamethasone increased the anesthetic success in comparison with placebo (n = 502; p < 0.001; OR = 2.59; 95% CIs: 1.46 to 4.59). Moreover, patients who were given dexamethasone had lower pain scores at 6 h (n = 302; p < 0.001; MD= −1.43; 95% CIs: −2.28 to −0.58), 12 h (n = 302; p < 0.0001; MD = −1.65; 95% CIs: −2.39 to −0.92), and 24 h (n = 302; p < 0.0008; MD = −1.27; 95% CIs: −2.01 to −0.53) when compared with placebo. In conclusion, the systemic administration of dexamethasone increases the anesthetic success rate and improves pain management in patients with SIP.